Ultrafast imaging of laser driven shock waves using Betatron x-rays from a laser Wakefield accelerator - Wood,JC; Chapman,DJ; Poder,K; Lopes,NC; Rutherford,ME; White,TG; Albert,F; Behm,KT; Booth,N; Bryant,JSJ; Foster,PS; Glenzer,S; et al. (Scientific Reports, 2018)
Betatron radiation from laser wakefield accelerators is an ultrashort pulsedsource of hard, synchrotron-like x-ray radiation. It emanates from a centimetrescale plasma accelerator producing GeV level electron beams. In recent yearsbetatron radiation has been developed as a unique source capable of producinghigh resolution x-ray images in compact geometries. However, until now, theshort pulse nature of this radiation has not been exploited. This reportdetails the first experiment to utilise betatron radiation to image a rapidlyevolving phenomenon by using it to radiograph a laser driven shock wave in asilicon target. The spatial resolution of the image is comparable to what hasbeen achieved in similar experiments at conventional synchrotron light sources.The intrinsic temporal resolution of betatron radiation is below 100 fs,indicating that significantly faster processes could be probed in futurewithout compromising spatial resolution. Quantitative measurements of the shockvelocity and material density were made from the radiographs recorded duringshock compression and were consistent with the established shock response ofsilicon, as determined with traditional velocimetry approaches. This suggeststhat future compact betatron imaging beamlines could be useful in the imagingand diagnosis of high-energy-density physics experiments.